Sulfinic Acids in Organic Synthesis: A Review of Recent Studies. Issue 8 (9th July 2021) - Bao, Ruwei; Feng, Yanping; Deng, Danfeng; Huang, Dayun; Sun, Xiangyu
Abstract: Decade advances of sulfinic acids (2010‐2021) were summarized via four categories by mechanisms: (1) sulfonyl radicals (2) RS radicals; (3) electrophilic intermediates; (4) nucleophilic S‐reagents. Their reactions with alkenes, alkynes, propiolic acids, cinnamic acids, allenes, ynones, azides, enynals, aldehydes, ketones, o ‐aryl isocyanides, arenes, quinoline N ‐oxides, disulfides, diselenides, thiophenol, P(O)‐H compounds, nitriles, alcohols, nitroso benzenes and dizo compounds will be discussed. Abstract : Decade advances of sulfinic acids (2010‐2021) were summarized via four categories by mechanisms: (1) sulfonyl radicals (2) RS radicals; (3) electrophilic intermediates; (4) nucleophilic S‐reagents.